2016
DOI: 10.3847/1538-4357/833/2/286
|View full text |Cite
|
Sign up to set email alerts
|

A Profile Analysis of Raman-Scattered O Vi Bands at 6825 Å and 7082 Å in Sanduleak’s Star

Abstract: We present a detailed modeling of the two broad bands observed at 6825 and 7082 Å in Sanduleak's star, a controversial object in the Large Magellanic Cloud. These bands are known to originate from Raman scattering of O VIλλ 1032 and 1038 photons with atomic hydrogen and are only observed in bona fide symbiotic stars. Our high-resolution spectrum obtained with the Magellan Inamori Kyocera Echelle spectrograph at the Magellan-Clay Telescope reveals, quite surprisingly, that the profiles of the two bands look ve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

6
0

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Many Raman scattered O vi features show double or triple peak profiles. Lee & Kang (2007) undertook profile analyses of the two symbiotic stars V1016 Cygni and HM Sagittae to show that the double peak profiles in these objects are well fit by adopting a Keplerian accretion disk around the hot white dwarf component (see also Heo & Lee 2015;Heo et al 2016). The fitted profiles are consistent with the O vi emission region in Keplerian motion with ∼ 50 km s −1 implying the physical dimension of the accretion disk ≤ 1 au.…”
Section: Introductionmentioning
confidence: 88%
“…Many Raman scattered O vi features show double or triple peak profiles. Lee & Kang (2007) undertook profile analyses of the two symbiotic stars V1016 Cygni and HM Sagittae to show that the double peak profiles in these objects are well fit by adopting a Keplerian accretion disk around the hot white dwarf component (see also Heo & Lee 2015;Heo et al 2016). The fitted profiles are consistent with the O vi emission region in Keplerian motion with ∼ 50 km s −1 implying the physical dimension of the accretion disk ≤ 1 au.…”
Section: Introductionmentioning
confidence: 88%
“…Subsequent studies reveal that the Raman O VI features provide strong constraints on the kinematics of emission nebulae around the white dwarf and extend our understanding of the mass loss process in symbiotic systems (e.g. Heo et al 2016).…”
Section: Raman O VI Features and Accretion Flowmentioning
confidence: 55%
“…In particular, a small sample of SySts with known Raman OVI bands have been observed in order to characterize the sensitivity of our method to Raman OVI emission of different intensities against different types of local continua. An example of GMOS-S/RAMSES II images of Sanduleak's star (Heo et al 2016), a SySt in the Large Magellanic Cloud, is shown in Fig. 1.…”
Section: Early Results From the Filter Acceptance Test At Gemini-southmentioning
confidence: 99%